Effect of a cationic corrosion-induced interface heterojunction on oxygen evolution reaction - Li Wang; Jun Lu; Hui Wang; Jianwei Ren (Chemical Engineering Journal Advances, 2022)
The creation of interface heterojunction could be an effective strategy to improve the activity of the catalysts for oxygen evolution reaction (OER). In this work, chain-like CoB alloy was firstly synthesized by magnetic field induction, and cationic corrosion approach was applied to create a heterojunction between NiFe layered double hydroxide (LDH) and magnetic CoB alloy surfaces. The results showed that OER performance was improved by achieving a current density of 10 mA cm−2 on the NiFe LDH@CoB electrode at an overpotential of 280 mV. The heterojunction of NiFe/LDH provided the catalytic sites and CoB alloy served as a good conductive support by improving the electron transfer rate.